2017
DOI: 10.1080/1369183x.2017.1314609
|View full text |Cite
|
Sign up to set email alerts
|

Attracting the best talent in the context of migration policy changes: the case of the UK

Abstract: Employment projections and skills strategies emphasise the importance of (highly)-skilled labour for competitiveness. A strategic focus on 'attracting the best talent' globally may conflict with policies to 'grow local talent'. This issue is considered in the UK context of a shift from a liberal immigration regime to a demand-led system characterised by increasing restriction, through adjustments to a points-based system to manage labour migration from outside the European Economic Area (EEA). The specific foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Furthermore, they describe how demand for labour implicitly determines how a father's advice leads a young migrant to study engineering rather than art. Green and Hogarth (2017)'s paper fits under the theme of institutions and policy, but the authors also acknowledge that policies are crucial to whether migrants are eligible for a destination and, if so, which destination they choose -while destination choice is also influenced by labour market shortages. In short, distinguishing between three themes and ordering the papers under these themes was useful to structure this introduction to the special issue, but the themes clearly intersect and the dividing lines between the themes and groups of papers are permeable.…”
Section: Inter-linkages Between the Themesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they describe how demand for labour implicitly determines how a father's advice leads a young migrant to study engineering rather than art. Green and Hogarth (2017)'s paper fits under the theme of institutions and policy, but the authors also acknowledge that policies are crucial to whether migrants are eligible for a destination and, if so, which destination they choose -while destination choice is also influenced by labour market shortages. In short, distinguishing between three themes and ordering the papers under these themes was useful to structure this introduction to the special issue, but the themes clearly intersect and the dividing lines between the themes and groups of papers are permeable.…”
Section: Inter-linkages Between the Themesmentioning
confidence: 99%
“…In the last paper of this special issue, Green and Hogarth (2017) bring institutional factors to the forefront of discussion by connecting migration policy changes and employer perspectives in the UK. Employers often face difficulties in adapting their businesses to changing rules.…”
Section: Institutions and Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, academic studies examining how more restrictive policy choices impacted employers hiring non-EEA migrants have already shown the variety of burdens businesses face and concluded that developing local talent, a plan often championed by politicians, only represents a partial solution to solving labour shortages (e.g. Green and Hogarth, 2017).…”
Section: Low-skilled In Theory: Definitions and Criticismmentioning
confidence: 99%
“…Other factors such as the role of government policies and bureaucratic system efficiency, the regulatory framework, the complexity of administrative procedures and the level of corruption are also thought to be important on the evolution of entrepreneurship, (Fogel et al 2006;Bowen and De Clercq 2008;Levie and Autio 2008;Bao et al 2016). A number of studies have demonstrated the impact of governmental policies in shaping skilled migration from the perspective of the political climate and economic situation (Boucher and Cerna 2014;Cerna 2014;Green and Hogarth 2017). Based on the above theoretical discussions pertaining to the interaction between institutions and entrepreneurship and skilled migrants, this study focuses on institutional features and examines specifically how the Chinese state promotes the return of diasporic Chinese technopreneurs as an economic engine of innovation, and furthermore, how the government affects diaspora returnees' technopreneurship through a top-down manner by way of direct policy and regulatory initiatives.…”
Section: Introductionmentioning
confidence: 99%